Synthetic Pyridoindole and Rutin Affect Upregulation of Endothelial Nitric Oxide Synthase and Heart Function in Rats Fed a High-Fat-Fructose Diet - Salvaras, Lazaros; Kovačič, Tomáš; Janega, Pavol; Lipták, Boris; Sasváriová, Michaela; Michalikova, D; Tyukos Kaprinay, Barbara; Bezek, Štefan; Sotníková, Ružena; Knezl, Vladimír; Stankovičová, Tatiana; Gáspárová, Zdenka (Physiological research, 2021)
Metabolic syndrome (MetS) belongs to the serious health complications expanding in cardiovascular diseases, obesity, insulin resistance, and hyperglycemia. In this study, hypertriacylglycerolemic rats fed a high-fat-fructose diet (HFFD) were used as an experimental model of MetS to explore the effect of tested compounds. Effects of a new prospective pyridoindole derivative coded SMe1EC2 and the natural polyphenol rutin were tested. Endothelial nitric oxide synthase (NOS3) and nuclear factor kappa B (NF-?B) expression were assessed in the left ventricle immunohistochemically and left ventricle activity was monitored in isolated perfused rat hearts. NOS3 activity in the left ventricle decreased markedly as a result of a HFFD. NOS3 expression was upregulated by both substances. NF-?B expression was increased in the MetS group in comparison to control rats and the expression further increased in the SMe1EC2 treatment. This compound significantly improved the coronary flow in comparison to the control group during reperfusion of the heart followed after ischemia. Further, it tended to increase left ventricular systolic pressure, heart product, rate of maximal contraction and relaxation, and coronary flow during baseline assessment. Moreover, the compound SMe1EC2 decreased the sensitivity of hearts to electrically induced ventricular fibrillation. Contrary to this rutin decreased coronary flow in reperfusion. Present results suggest that despite upregulation of NOS3 by both substances tested, pyridoindole SMe1EC2 rather than rutin could be suitable in treatment strategies of cardiovascular disorders in MetS-like conditions.
Keywords: indoly; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; biometrie; Indoles; rutin; Rutin; fruktosa; zvířata; Pyridines; Biometry; potkani Wistar; metabolický syndrom; Rats, Wistar; Male; Metabolic Syndrome; Heart; pyridiny; synthasa oxidu dusnatého, typ III; myokard; Animals; NF-kappa B; Myocardium; mužské pohlaví; Fructose; Nitric Oxide Synthase Type III; srdce